ASSESSING THE EFFECT OF FEDERAL UNIVERSITIES ACADEMICS AND NATIONAL YOUTH SERVICE CORPS MEMBERS ON THE CONDUCT OF GENERAL ELECTIONS IN NIGERIA - Aliyu, Kolawole M (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
This study examined salient issues that necessitated the use of federal universities academics and national youth service corps members as ad-hoc staff on the conduct of general elections in Nigeria and discussed the credibility of election management with the use of universities academics and national youth corps members. It also interrogated the effectiveness of the use of federal universities academics and national youth service corps members on election management and examined the challenges that faced their use by the Independent National Electoral Commission (INEC).The study utilized both primary and secondary data. The primary data was collected through semi-structured interviews with thirty respondents. Secondary data was sourced from newspapers, textbooks, magazines, journals, election manuals, and electoral act of 2010 as amended.The data collected wereanalysed using content analysis.The study showed that the need to sanitize the electoral system to make it more credible informed theoption of using universities academics and national youth service corps members as INEC ad-hoc staff. The study also showed that the academics and national youth service corps members have facilitated the credibility of the electoral system, and that the activities of desperate politicians who are driven by the lust for political power to achieve their inordinate desires are some of the challenges faced by the INEC inusing university academics and national youth service corps members. The study offered some recommendations to sustain the current use of universities academics and national youth service corps members in the conduct of future elections, given the improvement it has brought to the conduct of recent elections in Nigeria.